Educational Software as a Didactic Method in the Teaching of Multiplication of Tables (Docentes 2.0 Journal, 2021)
Today mathematics is still a significant obstacle in the formation of children since they observe it with fear and displeasure in their learning process teachers. In most cases, they base their teaching methods in a traditional and rote way, causing students to lack interest and motivation in this area. For this reason, the objective of this research was to design educational software to help strengthen the concepts of multiplication in second-grade primary school students. The study was carried out under the research-action methodology, based on the Escuela Nueva pedagogical model; the study was carried out on 15 students from the school of the Santa Ana village of the city of Duitama. Similarly, as it applied information gathering instruments, a diagnostic test, a completion test, and a final interview, results established the impact of educational software on the teaching of multiplication tables. The results obtained showed the importance of implementing tools such as educational software in the learning of multiplication tables, where it is essential to show teachers the usefulness of this material to use them to improve teaching and learning processes in students. In this way, motivation was generated, allowing them to acquire skills and competencies in mathematics according to how it is presented today.
Keywords: Educational software; teaching method; multiplication tables